Going the extra mile – creating a co-operative model for supporting patient and public involvement in research. Issue 1 (December 2016) - Horobin, Adele
Plain English summary In 2014, the Chief Medical Officer and Director General of Research and Development commissioned a review of patient and public involvement in the National Institute for Health Research. The report on this review, entitled 'Going the Extra Mile' was published in March, 2015. It described the bold goal of expecting all people using health and social care, and increasing numbers of the public, to be aware of and choosing to be involved in research. This requires more effort to build public awareness of research and better support for the public and researchers to do patient and public involvement in research. The author has created a new way of providing support for patient and public involvement based on co-operation between organisations. Termed 'share-banking', this model pools limited resources across organisations to deliver a regional programme of support activities for patient and public involvement over the long term. This includes helping organisations to share and learn from each other to avoid 're-inventing wheels' (where separate organisations each develop the same thing from the beginning). The 'Going the Extra Mile' report recommends that local organisations should work together to deliver public involvement activities across a region. 'Share-banking' should help fulfil this recommendation. Abstract The 'Going the Extra Mile' final report opened with the ambition to increase the public's awareness, participation and involvement in research. It stated the need for public and researchers to be better supported to do public involvement. A new co-operative model, termed 'share-banking', has been developed whereby organisations pool limited resources to create and sustain support for patient and public involvement in research. This should fulfil the 'Going the Extra Mile' report's recommendation to take a collaborative, cross-organisational and regional approach to public involvement.